2012
DOI: 10.5935/1678-9741.20120092
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression of endothelin receptors in replaced rheumatic mitral stenotic valves

Abstract: Objectives: Rheumatic fever is a highly prevalent disease in Brazil, and it poses a major public health problem. It is the leading cause of acquired heart disease in childhood and adolescence. The aim of this study was to evaluate the gene expression of ET-3 and its receptors, in replaced rheumatic mitral valves.Methods: We studied the gene expression of endothelin-3 (ET-3) and its receptors, endothelin receptor A and endothelin receptor B (ETr-A and ETr-B), in the rheumatic mitral valves of 17 patients who un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
1
1
0
1
Order By: Relevance
“…In our study, there is gene expression of endothelin-1 in damaged heart valves in patients that underwent mitral valve replacement, resembling those seen in other samples of the Brazilian population. In this sense, Moura et al [ 1 ] found that 40.7% of mitral valves (fibrosed and stenosed) replaced in patients with RF presented gene expression of ET-1 and, in our previous study [ 22 ] , we observed expression of both endothelin receptors (ETrA and ETrB) in replaced rheumatic mitral valves.…”
Section: Discussionsupporting
confidence: 52%
“…In our study, there is gene expression of endothelin-1 in damaged heart valves in patients that underwent mitral valve replacement, resembling those seen in other samples of the Brazilian population. In this sense, Moura et al [ 1 ] found that 40.7% of mitral valves (fibrosed and stenosed) replaced in patients with RF presented gene expression of ET-1 and, in our previous study [ 22 ] , we observed expression of both endothelin receptors (ETrA and ETrB) in replaced rheumatic mitral valves.…”
Section: Discussionsupporting
confidence: 52%
“…Por fim, também foram observados fibroblastos, linfócitos e áreas de calcificação distrófica (necrose tecidual) e fibrose em todas as amostras analisadas. 6 Brazilian Journal of Health Review, Curitiba, v. 5, n. 6, p. 22514-22524, nov./dec., 2022 A EM reumática leva a um aumento da pressão no átrio esquerdo, gerando assim também um aumento da contração do AE. No entanto eventualmente pode ocorre um remodelamento do AE, em decorrência de taquicardia e sobrecarga crônica de pressão, que desencadeia diversas alterações histológicas dentre elas hipertrofia, necrose e apoptose vindo então a gerar um possível quadro de fibrilação atrial.…”
Section: Fisiopatologiaunclassified
“…Rheumatic fever (RF) is a recurring, inflammatory and autoimmune disease as a result of complications of infections by Lancefield group A β-hemolytic Streptococcus pyogenes. RF is rare in developed countries but remains a disease with high prevalence in developing countries, and is a major cause of acquired heart diseases in children and young adults, such as mitral or aortic stenosis [ 3 - 6 ] . It is estimated that more than 125000 people are hospitalized per year in Brazil because of acute RF [ 7 ] .…”
Section: Introductionmentioning
confidence: 99%